SISTEM INVENTARIS TRANSFORMATIF: MEMANFAATKAN BLOCKCHAIN DAN LARAVEL DI PT. MANDIRI PLASTINDO - sanjay, sanjay; Maulana, Donny; Kurniadi, Nanang Tedi (IDEALIS : InDonEsiA journaL Information System, 2024)
Transformative Inventory System: Utilizing Blockchain and Laravel at PT. Mandiri Plastindo The aim of this research is to develop and execute a system. Transformative Inventory utilizes Blockchain technology and the Laravel framework at PT. Mandiri Plastindo. The problem raised is efficiency and reliability in inventory management which can be improved through the application of the latest technology. The proposed Waterfall model SDLC method involves developing a Blockchain-based system to secure and track inventory changes in a transparent and immutable manner. The Laravel framework is used to build application platforms that are user-friendly and easy to develop. A web-based application is the result of this research. allows PT. Mandiri Plastindo to efficiently manage their inventory by increasing speed, security and reliability. With Blockchain technology, inventory data can be clearly verified and cannot be manipulated, increasing trust and transparency in the inventory management process. The conclusion of this research is that implementing a transformative inventory system using Blockchain and Laravel can provide important benefits for businesses, including increased operational effectiveness, increased security of information and more openness in inventory management. The existence of an inventory system can make it easier to handle data on incoming and outgoing goods. Apart from that, it can speed up searching for stock and making stock reports. In addition, you can attach accurate stock reports. As a result, companies can optimize their business processes and achieve better overall performance